Argentina : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses the following issues related to the economy of Argentina: macro-financial performance and financial system overview, financial sector risks and resilience, financial safety nets, financial sector oversight framework, and financial sector development. Argentina's financial system is very small compared to countries at a similar stage of development and it is mostly transactional. Building greater confidence in the macroeconomic outlook is essential to deepening financial markets. The banking system appears resilient to a wide range of shocks, reflecting banks' large capital and liquidity buffers, as well as the strong quality of their assets. Continuing to improve the financial infrastructure would also help enhance access to finance.